2021
DOI: 10.1111/1750-3841.15696
|View full text |Cite
|
Sign up to set email alerts
|

Soyasaponin ameliorates obesity and reduces hepatic triacylglycerol accumulation by suppressing lipogenesis in high‐fat diet‐fed mice

Abstract: Soyasaponins are triterpenoid glycosides found in soybean. We investigated whether soyasaponin ameliorates lipid metabolism and its possible mechanisms. In C57BL/6J mice fed a high‐fat diet (HFD), soyasaponin (SAP) was orally administered for 9 weeks. Additionally, we evaluated the effect of soyasapogenols on 3T3‐L1 adipocytes. In HFD‐fed mice, the SAP significantly reduced body weight by 7% and relative adipose tissue weight by 35%. X‐ray computed tomography demonstrated that the SAP reduced visceral and subc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 64 publications
0
11
0
Order By: Relevance
“…[108] identified several soyasaponins, sapogenins, and isoflavones in soy root exudates. Soyasaponins have been linked to anti-obesity, anti-oxidative stress, and anti-inflammatory properties, as well as preventive effects on hepatic triacylglycerol accumulation [123][124][125][126]. Omar et al [127] identified the potent inhibitory effects of soyasapogenol A, which is a triterpenoid, against p53-deficient aggressive malignancies.…”
Section: Bioactive Compounds In Underused Soy Partsmentioning
confidence: 99%
“…[108] identified several soyasaponins, sapogenins, and isoflavones in soy root exudates. Soyasaponins have been linked to anti-obesity, anti-oxidative stress, and anti-inflammatory properties, as well as preventive effects on hepatic triacylglycerol accumulation [123][124][125][126]. Omar et al [127] identified the potent inhibitory effects of soyasapogenol A, which is a triterpenoid, against p53-deficient aggressive malignancies.…”
Section: Bioactive Compounds In Underused Soy Partsmentioning
confidence: 99%
“…The inhibitory activity of saponins against pancreatic lipase is considered one of the mechanisms underlying their anti-obesity effect [28]; however, in this study, addition of MPP to the HFD did not increase the fecal TG content, suggesting that pancreatic lipase activity was not inhibited by the compounds in MPP. Similarly, the antiobesity effects of soyasaponins and fermented soymilk were not associated with increased fecal lipid levels [30,33]. Moreover, soyasaponins did not inhibit pancreatic lipase in vitro, indicating that pancreatic lipase inhibition is not always involved in the anti-obesity effect of bioactive foods.…”
Section: Discussionmentioning
confidence: 94%
“…However, other triterpenoid saponins in foods and herbs have been shown to modulate metabolic pathways and thereby prevent obesity [28,29]. Recently, Tsai et al reported the anti-obesity effect of soyasaponins in HFD-fed C57BL/6J mice [30]. In addition, Wu et al demonstrated that oleanane and ursane-type triterpenoids isolated from Cyclocarya paliurus (CP) downregulated intestinal ApoB-48 secretion and that a hydroxy group at C-23 in the triterpenoid structure seemed to be essential for their activities [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the aglycone (soyasapogenol) structure, soyasaponins are mainly divided into two groups as A and B [11]. Soyasaponin A contains sugar moieties at the C-3 and C-22 positions of the ring structures [12]. Soyasaponin A has eight isomers, named as Aa-Ah [13].…”
Section: Introductionmentioning
confidence: 99%